1993
DOI: 10.1111/j.1365-2958.1993.tb01958.x
|View full text |Cite
|
Sign up to set email alerts
|

Theta replication of the lactococcal plasmid pWVO2

Abstract: pWVO2 is a 3.8 kb narrow-host-range plasmid from Lactococcus lactis ssp. cremoris Wg2, which does not replicate in Bacillus subtilis or Escherichia coli. Single-stranded pWVO2 DNA was not observed in lactococcal cells, indicating that this plasmid does not replicate via a rolling-circle mechanism. The sequence of pWVO2 neither showed the structural organization typical for rolling-circle plasmids, nor were sequence similarities with known rolling-circle plasmids present. By 2-D agarose gel electrophoresis of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 40 publications
3
83
0
Order By: Relevance
“…The complementation of prsA3 was determined with IH7492 (prsA3 trpC2 glyB133 hisA1), which expresses amyQ of Bacillus amyloliquefaciens from pKTH3382. The pKTH3382 plasmid was constructed by inserting the amyQ gene as a SalI fragment into pSR11 (22). IH7492 was also used as the parental strain to produce and purify various lipomodified PrsA proteins.…”
Section: Methodsmentioning
confidence: 99%
“…The complementation of prsA3 was determined with IH7492 (prsA3 trpC2 glyB133 hisA1), which expresses amyQ of Bacillus amyloliquefaciens from pKTH3382. The pKTH3382 plasmid was constructed by inserting the amyQ gene as a SalI fragment into pSR11 (22). IH7492 was also used as the parental strain to produce and purify various lipomodified PrsA proteins.…”
Section: Methodsmentioning
confidence: 99%
“…To date, the replication regions of more than 20 lactococcal plasmids have been sequenced and have been shown to belong to the highly homologous pCI305-type family (21), of which pWV02 has been shown to replicate via the mode (27). On the basis of homologies and structural organization, these plasmids can be considered class A plasmids.…”
mentioning
confidence: 99%
“…In some related plasmid replicons, the oni has been further localized to regions that contain only the 22-bp iterons and the 10-bp direct repeats (Frere et al, 1993;Kiewiet et al, 1993a;Pedersen et al, 1994). It is now believed that the Rep proteins in these plasmids bind to their 22-bp iterons to initiate replications (Kiewiet et al, 1993a;Seegers et al, 1994). Another notable feature is the presence of two inverted repeats (IR1 and IR2) which span the putative promoter site in the FG2 plasmid replicon.…”
Section: Discussionmentioning
confidence: 99%
“…lactis FG2. To date, three lactococcal plasmid replicons, pUCL22 (Frere et al, 1993), pWV02 (Kiewiet et al, 1993a) and pCT1138 (Pedersen et al, 1994), have been characterized extensively and shown to replicate in L. lactis by the theta-replicating mechanism. Other members of this family are all closely related.…”
Section: Discussionmentioning
confidence: 99%